2021
DOI: 10.30773/pi.2020.0304
|View full text |Cite
|
Sign up to set email alerts
|

Development of Random Forest Algorithm Based Prediction Model of Alzheimer’s Disease Using Neurodegeneration Pattern

Abstract: Objective Alzheimer’s disease (AD) is the most common type of dementia and the prevalence rapidly increased as the elderly population increased worldwide. In the contemporary model of AD, it is regarded as a disease continuum involving preclinical stage to severe dementia. For accurate diagnosis and disease monitoring, objective index reflecting structural change of brain is needed to correctly assess a patient’s severity of neurodegeneration independent from the patient’s clinical symptoms. The main aim of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Besides, it showed advantages in antinoise performance [26]. RF could process continuous and discrete data simultaneously [27] and possess significant advantages in processing high-dimension data, such as simplicity, realizability, and low computing cost [28]. The results of the research revealed that the prediction accuracy of RF training set samples reached 98.33%.…”
Section: Discussionmentioning
confidence: 97%
“…Besides, it showed advantages in antinoise performance [26]. RF could process continuous and discrete data simultaneously [27] and possess significant advantages in processing high-dimension data, such as simplicity, realizability, and low computing cost [28]. The results of the research revealed that the prediction accuracy of RF training set samples reached 98.33%.…”
Section: Discussionmentioning
confidence: 97%
“…GC-MS technology was used to determine the changes of volatile components in tobacco before and after mildew. Some studies have shown that substances with large changes are obtained by comparing before and after mildew, and then the content changes of these substances are used to establish a model, so as to infer whether it is mildew [2].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Teaching and research ability [23] includes the ability to carry out various special lectures; the ability to participate in the first and second classroom teaching work; and the ability to carry out theoretical research and project application in combination with work.…”
Section: Decision Tree Algorithm the Decision Tree Algorithmmentioning
confidence: 99%